EXPERIENCE OF RITUXIMAB APPLICATION ON A PATIENT, SUFFERING FROM JUVENILE RHEUMATOID ARTHRITIS - E.I. Alexeeva; T.М. Bzarova; E.L. Semikina; S.S. Akulova ("Paediatrician" Publishers LLC, 2006)
The article describes the run of the severe systemic juvenile rheumatoid arthritis, which is resistant to the standard antirheumatic therapy. The disease was characterized by such systemic implications of the disease, as: fever, rash, pericarditis, lymphadenopathy, hepatomegaly accompanied by the generalized joint syndrome and high laboratory indices of activity. Introduction of rituximab into the treatment scheme allowed the researchers to decrease the general activity of the disease, arrest the systemic implications, improve functional status of the joints, and normalize the laboratory indices of activity. The effect duration was 5 months and 4 months after the first and second course of treatment by rituximab accordingly. The treatment results prove the perspective of rituximab application with in the complex therapy for the patients, suffering from juvenile rheumatoid arthritis. However, it is necessary to conduct further research to identify the location of antibodies to cd 20+ within the therapy scheme of this disease. Key words: children, treatment, rituximab, juvenile rheumatoid arthritis.